Islamic Communication of Rumah Quran Aisyah In Increasing Interest In Learning The Quran In The Community of Tanjung Morawa - Mukhtar, Gazali; Rubino, Rubino; Ritonga, Hasnun Jauhari (Nazhruna: Jurnal Pendidikan Islam, 2023)
This qualitative type of research aims to explain the implementation, model, and impact of Islamic communication at Rumah Quran Aisyah Radliallahu'Anha in increasing public interest in learning the Quran in Tanjung Morawa. Information was obtained that the implementation of Islamic communication carried out by the manager of the Aisyah Radliallahu'Anha Quran House in increasing public interest in learning the Quran in Tanjung Morawa Deli Serdang was carried out by managers, teaching staff, and participants who had joined. They communicate it directly or through mass media, print, electronic, and internet/online. The communication runs Islamically in some moments, but in others, it only adopts Islamic values because the place and time are irrelevant. The Islamic communication model used is a persuasive communication model that is equivalent to da'wah communication and prophetic communication on the side of the stages passed.